2010
DOI: 10.1158/1535-7163.mct-09-0689
|View full text |Cite
|
Sign up to set email alerts
|

SB939, a Novel Potent and Orally Active Histone Deacetylase Inhibitor with High Tumor Exposure and Efficacy in Mouse Models of Colorectal Cancer

Abstract: Although clinical responses in liquid tumors and certain lymphomas have been reported, the clinical efficacy of histone deacetylase inhibitors in solid tumors has been limited. This may be in part due to the poor pharmacokinetic of these drugs, resulting in inadequate tumor concentrations of the drug. SB939 is a new hydroxamic acid based histone deacetylase inhibitor with improved physicochemical, pharmaceutical, and pharmacokinetic properties. In vitro, SB939 inhibits class I, II, and IV HDACs, with no effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 30 publications
7
95
0
Order By: Relevance
“…Therefore, concentrations of orally active givinostat used in vivo and in vitro in our study are clinically feasible, safe, and effective. Although we did not measure vorinostat plasma levels in the treated NOD mice, the dose used was clinically relevant, because oral administration of 50 mg/kg of vorinostat in mice in other studies resulted in a plasma concentrations equal to those obtained by safe and tolerated doses in humans (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, concentrations of orally active givinostat used in vivo and in vitro in our study are clinically feasible, safe, and effective. Although we did not measure vorinostat plasma levels in the treated NOD mice, the dose used was clinically relevant, because oral administration of 50 mg/kg of vorinostat in mice in other studies resulted in a plasma concentrations equal to those obtained by safe and tolerated doses in humans (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth inhibition was calculated as described previously. 10 For the efficacy studies, mice were treated by oral gavage (10 ml/kg body weight) with doses from 50 to 150 mg/kg SB1518.…”
Section: In Vivo Efficacy Studiesmentioning
confidence: 99%
“…(Table 3). Besides, induction of cell cycle arrest and elevated cleavage of poly ADP ribose polymerase (hallmark of apoptosis) in a dose-dependent manner was seen in the defined model upon the therapeutic intervention using pracinostat (Novotny-Diermayr et al 2010). Superior pharmacokinetic properties were seen for pracinostat compared to SAHA in nude mice models.…”
Section: Pracinostat In Colorectal Cancer Therapymentioning
confidence: 95%
“…Pracinostat has shown an average 2-fold greater potency than SAHA against classical HDACs excluding HDAC6. Experiments dealing with the comparative potency of pracinostat and FDA approved SAHA across distinct cell lines have clearly shown that the former inhibitor is 3.5-fold more potent than the latter on an average (Novotny-Diermayr et al 2010). However, in case of colorectal cancer cell line (HCT-116), pracinostat proved to be 7.6-fold more potent than SAHA (Pracinostat IC 50 ¼ 0.48 mmol/L and for SAHA 2.14 mmol/L).…”
Section: Pracinostat In Colorectal Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation